Glucagonoma syndrome demonstrating giant duodenal villi. Issue 7 (July 1984) - Stevens, F M; Flanagan, R W; O'Gorman, D; Buchanan, K D
Abstract : A 39 year old man developed an itchy bullous rash in the perineum and on the extremities. Six years later, after giant intestinal villi had been noted at endoscopy, a diagnosis of the glucagonoma syndrome was made. Investigation revealed a large tumour of the pancreatic body and tail. The molecular species of glucagon secreted by the tumour were characterised using the combined purification procedures of immunoaffinity chromatography followed by gel filtration.